Bibliometric and visualized analysis of sodium–Glucose cotransporter 2 inhibitors - Sun, He; Wang, Zhongqing; Wang, Yuxi; Rong, Haichuan; Wang, Danyang; Liu, Xiangnian; Jin, Ke; Sun, Zhicheng; Fan, Qiuling (Frontiers in Pharmacology, 2023)
Background: Sodium glucose cotransporter 2 (SGLT2) inhibitors have proved to be extremely effective and reliable in reducing hyperglycemia, and have also been used for the treatment of cardiovascular and renal disease in patients with or without type 2 diabetes. Thousands of research articles on SGLT2 inhibitors have been published in the past, but few bibliometric analyses have systematically been studied this field. We aimed to visualize the global research hotspots and trends of SGLT2 inhibitors using a bibliometric analysis to provide new evidence and ideas for researchers and clinicians in this field. Methods: We retrieved publications from Science Citation Index Expanded (SCI-Expanded) of Web of Science Core Collection (WoSCC) in 2004–2022 on July 1, 2022. Microsoft Excel, CiteSpace and VOSviewer were employed to collect publication data, analyze publication trends, and visualize relevant results. Results: We identified 4,419 original research articles on SGLT2 inhibitors published between 2004 and the first half of 2022. Global SGLT2 inhibitors-related research increased rapidly from 2004 to 2022, especially recently. USA made the greatest contribution to the topic, with (1,629, 36.86%) publications and citations (88,892). AstraZeneca was the most prolific institutions (272, 6.16%). Heerspink HJL published the most related articles (98), whereas Zinman B was cited the most frequently (1,784 citations). Diabetes Obesity & Metabolism was the journal with the most studies (406, 9.19%), and The New England Journal of Medicine was the most commonly cited journal (11,617 citations), with nine of the top 10 co-cited references published in this journal. The emerging keywords “heart failure,” “diabetic cardiomyopathy,” “ejection fraction,” “mortality,” “biomarker,” “fibrosis,” “ampk,” and “guideline” appeared the most recently as research frontiers. Conclusions: USA is the leader in SGLT2 inhibitor research. Recently, the research on SGLT2 inhibitors has focused on clinical trials, related mechanisms, and therapy. In the future, the research on SGLT2 inhibitors will delve into molecular mechanisms, especially those related to fibrosis and AMPK, revealing the link between SGLT2 inhibitors and heart failure and diabetic cardiomyopathy will be the next research hotspot.